(untitled) - Baxter, Pam M. (New York, 1995)
This new book examines the topics and issues important to information professionals and librarians-in-training who serve clientele using social science materials. Social Science Reference Services addresses reference services across the spectrum of the social sciences and embraces a multidisciplinary approach to providing both materials and services to users
Keywords: Social sciences,Reference services (Libraries); Bibliography,Methodology; United States